The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1124/dmd.30.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and Mercapturic Acid Conjugates of Sulofenur and Their Activity against a Human Colon Cancer Cell Line

Abstract: ABSTRACT:Sulofenur is one of the diarylsulfonylureas developed as an anticancer agent. Sulofenur possesses a broad spectrum of activity in several solid tumor models and has undergone extensive clinical trials based on its impressive preclinical activity. However, the clinical response of sulofenur has been disappointing because of the side effect of anemia. Furthermore, the anticancer mechanism of sulofenur and its diarylsulfonylurea analogs still remains unknown. Elucidation of the metabolic fates of sulofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…Therefore, increased activity or abundance of GST may facilitate the formation and subsequent accumulation of such compounds. It is also important to note that quercetin can inhibit GST through the formation of oquinone (18,31) and other GSH, and mercapturic conjugates inhibit GSH reductase (28). Therefore, in tyrosinase expressing cells, quercetin may have multiple modes of interaction with drug detoxification proteins and may provide a means to interfere with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increased activity or abundance of GST may facilitate the formation and subsequent accumulation of such compounds. It is also important to note that quercetin can inhibit GST through the formation of oquinone (18,31) and other GSH, and mercapturic conjugates inhibit GSH reductase (28). Therefore, in tyrosinase expressing cells, quercetin may have multiple modes of interaction with drug detoxification proteins and may provide a means to interfere with drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Tyr + cells may also display elevated GST activity and a higher capacity to form conjugates. Various GSH and mercapturic acid conjugates have anticarcinogenic activity (28) and chemopreventative properties (29). The role of conjugate toxicity is further demonstrated by the induction of apoptosis in cells after the depletion of ralA binding protein 1, a transporter of GSH conjugates (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was clearly demonstrated that SCPG is further processed through the mercapturic acid pathway to the corresponding N-acetylcysteine conjugate [ N -acetyl- S -( p -chlorophenylcarbamoyl)cysteine, NACC], which possesses comparable anticancer activity to the parent compound. The GSH- and cysteine-conjugates produced are susceptible to thiol exchange reactions and may act as carbamoylating agents towards biomacromolecules (Day et al, 1996; Guan et al, 2002). NACC, whose mechanism of action remains unclear, demonstrated selective anticancer activity, and low toxicity, which make NACC and its analogs promising anticancer agents (Chen et al, 2011).…”
Section: Bioactivation Of Cancer Compounds By Gstmentioning
confidence: 99%
“…Therefore, though urinary MAs are frequently used as biomarkers of internal dose, they are sometimes also classified as biomarker of effect [22]. Several recent and older examples of MAs used in the BM of human exposure or in biotransformation studies are: N-acetyl-S-(9,10-dihydro-9-hydroxy-10-phenanthryl)-L-cysteine, which originates from a polycyclic aromatic hydrocarbon, phenanthrene, present in cigarette smoke [23], four structurally different mercapturates derived from the herbicides atrazine, acetochlor, metolachlor, and alachlor [24], S-acetamidomethylmercapturic acid, in response to exposure to the industrial solvent N,N-dimethylacetamide [25], N-acetyl-S-(p-chloro- phenylcarbamoyl)cysteine, derives from the anticancer agent sulofenur [26], phenyl mercapturic acid, in response to benzene exposure in industry [27], 3,4-dihydroxybutylmercapturic acid as an environmental and biological monitoring indicator of non-occupational exposure to 1,3-dichloropropene [28], 3-chloro-2-hydroxypropylmercapturic acid and allylmercapturic acid as urinary biomarkers of human exposure to allyl chloride [29], and N-acetyl-S-(Z-and E-3-chloropropenyl-2)-L-cysteine as a biomarker for agricultural soil fumigant 1,3-dichloropropene [30]. In the first part of the studies summarized in this Review, attention is paid to MA derivatives of volatile anesthetics in humans, and whether they are applicable as biomarkers of effect.…”
Section: Mercapturic Acids: Potential Biomarkers Of Effectmentioning
confidence: 99%